Resistant genotypes combined with high elevation level provide bacterial wilt control in potato (Solanum tuberosum L.) in the Western Highlands zone of Cameroon. (October 2022) - Anoumaa, Mariette; Kanmegne, Gabriel; Suh, Christopher; Kouam, Eric Bertrand; Djomo Sime, Hervé; Temfack Deloko, Carlos Dély; Fonkou, Théophile
Abstract: Potato production in Cameroon is constrained by biotic factors including bacterial wilt disease caused by Ralstonia solanacearum . No single method effectively controls this disease. Breeding for resistance is usually the best option for disease control in crops. Screening the potential parents for resistance under the target environmental conditions is the prerequisite for effective resistance breeding. This study aimed to determine the response to bacterial wilt of selected potato genotypes grown under different elevation levels and to identify suitable parents that can be used to develop resistant cultivars. The study was carried out in three elevations [high (>1800 m above sea level (m.a.s.l)), medium (1400–1800 m.a.s.l) and low (<1400 m.a.s.l)] in the Western Highlands zone of Cameroon. Seven potato genotypes were planted in a field of each elevation using a Complete Randomized Block Design with three replications. Inoculation occurred naturally. Disease parameters collected included days to onset wilting and bacterial wilt incidence (BWI). Yield components such as the total number of tubers per plant, the percentage of unmarketable tubers and the marketable yield were recorded. BWI as well as the percentage of unmarketable tubers decreased with elevation, meanwhile marketable yield increased with elevation. Disease development tended to be lower in all cultivars at higher elevations. The resistance of Dosa, Desiree, and Banso was high in all environments. based on these results, the combination of these two methods can lower the impact of bacterial wilt. Dosa can be grown at higher elevation fields for stable and higher yields. Highlights: The combination of high elevation and resistant cultivars can lower the impact of bacterial wilt disease in potato. High elevation exhibits low temperatures which limit the spread of the disease. Low temperatures are more suitable for potato tuberization. Genotype Dosa can be grown at higher elevation fields for stable and higher yields in the West of Cameroon. Dosa, Desiree, and Banso genotypes can be used as suitable parents to breed resistant cultivars.